Triazole-, piperazine-, and DOPO-containing eugenol-based reactive flame retardant for unsaturated polyester resin - ÇAKMAKÇI, EMRAH (My University, 2024)
The flammability of unsaturated polyester resins (UPRs) limits their applications. Herein, a reactive P- and N-containing flame retardant (DPET) having triazole and piperazine rings is reported. The 9,10-Dihydro-9-oxa-10-phosphaphenanthrene 10-oxide (DOPO) was used to introduce P atoms, and eugenol was used to import reactive double bonds to DPET. Different ratios of DPET were mixed with a commercial UPR and the thermal, mechanical, optical, and flame retardancy properties were measured. The addition of 15% of DPET into neat UPR led to a decrease in the water contact angle from 70° ± 2 to 61° ± 2. The gel content values of the UPRs were found to change between 97.5% and 89%. The optical properties of the UPR were adversely affected by the incorporation of DPET. The modulus of the DPET-containing UPRs increased with increasing amount of DPET and 15% of DPET-containing UPR displayed a modulus value of 1784 ± 86 MPa. When 15% DPET was added to neat UPR, char yields were increased (from 5.6% to 16.6%). Limiting oxygen index (LOI) values increased with increasing amounts of DPET and reached up to 23.4%. Micro cone calorimeter (MCC) test results showed up to a 20.5% reduction in the peak heat release rate (PHRR) of the UPR when 15% DPET was added.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik Bilişim Ve Teknoloji (Eng); Temel Bilimler (Sci); Malzeme Bilimi; Malzeme Bilimi Çokdisiplinli; Polimer Bilimi; Kimya Fiziksel; Engineering Computing & Technology (Eng); Natural Sciences (Sci); Materials Science; Materials Science Multidisciplinary; Polymer Science; Chemistry Physical; Genel Kimya; Fizik Bilimleri; Yüzeyler, Kaplamalar ve Filmler; Polimerler ve Plastikler; Malzeme Kimyası; General Chemistry; Physical Sciences; Surfaces, Coatings and Films; Polymers and Plastics; Materials Chemistry; flame retardance; radical polymerization; resins; thermal properties; thermosets